2021
DOI: 10.1016/j.molcel.2021.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Remdesivir is a delayed translocation inhibitor of SARS-CoV-2 replication

Abstract: Highlights d Kinetics show stalling after 3-4 remdesivirs are incorporated d The stalled complex partially escapes in the presence of high NTP concentrations d Stalling is due to a block in translocation after incorporation of the fourth RMP d The translocation block is a steric clash between the cyano group of RMP and the protein

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 31 publications
3
99
0
1
Order By: Relevance
“…While the S861A mutant shows a subtle reduction in delayed chain-termination [ 26 , 27 •• ], RNA synthesis is not inhibited with the S861 G mutant [ 27 •• ]. These results guided structural studies that confirmed the original model [ 28 , 29 ].
Figure 1 How does RDV work against SARS-CoV-2?
…”
Section: Delayed Chain-terminationsupporting
confidence: 77%
“…While the S861A mutant shows a subtle reduction in delayed chain-termination [ 26 , 27 •• ], RNA synthesis is not inhibited with the S861 G mutant [ 27 •• ]. These results guided structural studies that confirmed the original model [ 28 , 29 ].
Figure 1 How does RDV work against SARS-CoV-2?
…”
Section: Delayed Chain-terminationsupporting
confidence: 77%
“…Nevertheless, remdesivir is virostatic by blocking the RNA translocation. Cryo-EM reconstruction of a remdesivir-stalled RNA-dependent RNA polymerase complex revealed that three or four remdesivir monophosphates are incorporated in the active site [ 52 ]. Therefore, remdesivir serves as a suitable positive control due to its strong virus inhibition in cell culture models [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…A key advantage for Rdv over other nucleotide analogues is its enhanced selectivity over ATP by SARS/MERS-CoVs RdRps [124] , [125] . Following incorporation of Rdv-TP, the RdRp elongates until stalling when the Rdv 1′-ribose cyano group clashes with the sidechain of nsp12 S861, hindering further translocation [124] , [125] , [126] , [127] , [128] ( Fig. 9 ).…”
Section: Antivirals Targeting the Rdrpmentioning
confidence: 99%
“…This observation led to initial descriptions of the mechanism of inhibition as delayed chain termination. However, under the saturating nucleotide concentrations occurring in the cellular milieu, the translocation block is surmounted [99] , [126] , [127] , [128] , suggesting that Rdv is incorporated throughout the nascently synthesized CoV genome [124] , [127] .
Fig.
…”
Section: Antivirals Targeting the Rdrpmentioning
confidence: 99%